Cadmium, lead, and zinc immobilization in soil by rice husk biochar in the presence of low molecular weight organic acids. Issue 16 (16th July 2022) - Islam, Md. Shoffikul; Song, Ziteng; Gao, Ruili; Fu, Qingling; Hu, Hongqing
ABSTRACT: Heavy metal immobilization using biochar (BC) is different from the usual soil incubation due to the low molecular weight organic acids (LMWOAs) in the rhizosphere and is an issue worth evaluating. Therefore, the impacts of rice husk BC (5%), tartaric acid, and oxalic acid, coupled with combinations of BC and tartaric acid/oxalic acid on the transformation of cadmium (Cd), lead (Pb), and zinc (Zn) among their geochemical forms, including their bioavailability in a metal-contaminated soil, were investigated in an incubation experiment. The application of BC, low concentration of tartaric acid (2 mmol kg −1 soil) (TA2), and the combined BC plus a low level of tartaric acid (BC-TA2) markedly reduced the acid-soluble and available (CaCl2 -extractable) Cd, Pb, and Zn compared to control (CK) in which BC-TA2 was found to be the most effective treatment. The trends were reversed in the case of the high concentrations of tartaric acid (>5–20 mmol kg −1 soil), all levels of oxalic acid (2–20 mmol kg −1 soil), and the combined BC plus high levels of tartaric acid/oxalic acid treatments. The BC-TA2 transformed the highest amounts of acid-soluble and reducible Cd, Pb, and Zn to the oxidizable and residual fractions with incubation time. The results suggested that the low concentration of tartaric acid enhanced Cd, Pb, and Zn immobilization, while the higher level of tartaric acid and all concentrations of oxalic acid increased their mobilization. In conclusion, BC-TA2 could immobilize the most heavy metals and serve as an amendment for metals' immobilization/redistribution in contaminated soils. GRAPHICAL ABSTRACT: UF0001